Forensics and Miscarriages of Justice: When Science Goes Wrong: Editorial - Kaukab Jamal Zuberi (International Journal for Electronic Crime Investigation, 2025)
In the minds of many, forensic science is the ultimate truth-teller in the criminal justice system. Television shows portray it as a flawless tool that can always find the real culprit and exonerate the innocent. But in the real world, things are far more complicated. While forensics can be incredibly powerful in solving crimes, it can also lead to tragic mistakes—sending innocent people to prison, or worse, to death row.